The Comparison of Chilli Varieties Suitable for Food Processing : Pepper Sauce - Kulvadee Trongpanich; Chowladda Teangpook; Ngamjit Lowitoon; Urai Paowsungthong (Agriculture and Natural Resources, 2002)
Seventeen varieties of chilli fruits planted at Kasetsart University were comparatively studied for the suitability for using as a raw material for green and red hot and sour pepper sauce production. The materials were determined for the yield of destemmed chilli fruit and the waste after straining. After production, the products were sensory evaluated by 21 experienced food tasters with BIB design, and hedonic preference scale. The data was analysed by SAS program. For red chilli, the average yield of the destemmed fresh chilli was 89.85% and the average waste after straining was 55.36%. The variety with the lowest quantity of waste after straining was CA 500, followed by CA 223, CA 133, CA 1107, CA 367, CA 1143 – B, CA 1018 – C, CA 161 and CA 1013 A respectively. All of these mentioned varieties gave the waste equal or lower than the average. The result from the sensory evaluation showed that CA 426 with the highest total preference score, color, and acceptability, got the high scores in appearance, odor, taste and texture that was not significantly different to the highest scores of the other samples in those characteristics. The control red pepper sauce sample got the lowest score in total preference score with significant difference in every character compared to the highest scores except odor and texture. For the green hot and sour pepper sauce, the average yield of the destemmed fresh chilli was 91.48% while the average waste after straining was 71.20%. The variety with the lowest amount of waste was CA 919, followed by CA 1013 – A, CA 1096 – C, CA 426, CA 133, CA 1012 – C, CA 1107; CA 367, and CA 1143 – B respectively. All of these mentioned varieties gave the waste lower than the average. From the sensory evaluation, CA 426 got the highest total preference score followed by CA 398, CA 1013 – A, CA 1018 – C and CA 1012 – C. CA 426 got the preference scores in every characteristic higher than the control green pepper sauce, except in color.